Atrophic mandible fracture approach by load-bearing system: case report - da Paixão Silva, Albert; Michel, Alejandro Favio Estrada; Santos, Elias Almeida dos; Rodrigues, Rafael Drummond; Carvalho, Ravy Silva (Revista Uningá, 2022)
Mandible fractures are the most frequent in the maxillofacial complex. Due to weakness and impaired reflexes, 10.1% to 56% of affected individuals are elderly. Thus, this study aimed to report a case report of a mandibular symphysis fracture in a total edentulous patient with an atrophic mandible treated through open surgery with a load-bearing device, demonstrating the management and characteristics relevant to this treatment. The 59-year-old male patient, melanoderma, attended the Oral and Maxillofacial Surgery and Traumatology Service of the General Hospital of the State, Bahia, after being a victim of a motorcycle accident, causing trauma to the face. The physical examination revealed, among other clinical signs, unstable maxilla and atypical mobility when manipulating the mandible. On imaging, there were signs suggestive of fracture of the mandibular symphysis, nasal bones, orbital zygomaticomaxillary complex, and Le Fort I maxillary fracture. A surgical approach allowed reduction and rigid internal fixation with a plate and 2.4mm system screws, while the middle third fractures followed a conservative treatment line. In the postoperative follow-up, there was an adequate fracture reduction and no signs of displacement of the fractured stumps. Furthermore, the patient had a satisfactory clinical recovery. In the literature, there is no consensus on the surgical approach and treatment of atrophic mandible fractures except by use of rigid fixation systems by load-bearing devices proved to be an effective alternative for fracture stabilization and consolidation in cases of mandibular atrophy as demonstrated in this work.